Knowledge, Attitude, and Behavior of Indonesian Breastmilk Donors via the Internet - Iva Septyani; Sri Umijati (Global Medical & Health Communication (GMHC), 2018)
Breastmilk donors are increasingly widespread and can be done by mothers easily and rapidly through the internet. This study aims to analyze the correlation of knowledge and attitudes of breastmilk donors to the behavior of breastmilk donors via the internet in Indonesia. The study used a cross-sectional analytic design and using a total sampling technique by sending research instruments in the form of the Google form was conducted in January–April 2017. The study respondents were breastmilk donors who posted information on their breastmilk to be shared through Facebook Human Milk 4 Human Babies Indonesia in Jakarta, Depok, Indramayu, Bandung, and others were totaling 41 respondents. Statistical analysis using the Spearman test with confidence level was α=0.05. The study results showed that the correlation to knowledge and behavior of breastmilk donors had p value=0.080, while the correlation on attitude and behavior of breastmilk donors had p value=0.715. In conclusion, there was no correlation between the attitude of breastmilk donors and the practice of breastmilk sharing via the internet. PENGETAHUAN, SIKAP, DAN PERILAKU PENDONOR ASI VIA INTERNET DI INDONESIADonor air susu ibu (ASI) semakin marak dan dapat dilakukan para ibu dengan mudah dan pesat melalui internet. Penelitian ini bertujuan mengetahui hubungan pengetahuan dan sikap pendonor ASI dengan perilaku donor ASI via internet di Indonesia. Penelitian ini merupakan penelitian desain analitik cross-sectional dan menggunakan teknik total sampling dengan mengirimkan instrumen penelitian dalam bentuk Google form yang dilakukan pada bulan Januari–April 2017. Responden penelitian adalah pendonor ASI yang mem-posting informasi ASI-nya untuk dibagikan melalui Facebook Human Milk 4 Human Babies Indonesia di Jakarta, Depok, Indramayu, Bandung, dan lain-lain yang berjumlah 41 responden. Analisis statistik menggunakan Uji Spearman dengan tingkat kepercayaan α=0,05. Hasil penelitian menunjukkan bahwa hubungan pengetahuan dengan perilaku pendonor ASI memiliki nilai p=0,080, sedangkan hubungan sikap dengan perilaku pendonor ASI memiliki nilai p=0,715. Simpulan, tidak terdapat hubungan pengetahuan dan sikap pendonor ASI dengan perilaku pendonor ASI via internet di Indonesia.